Pendidikan Islam dalam Spektrum Politik Pendidikan Nasional - mastur mastur (UIN Mataram, 2019)
Discourse on Islamic education will never be separated from the political and cultural dynamics of a society. In the Indonesian context, the dynamics of Islamic education cannot be separated even shackled by the country's political policies and community pluralism which is a reality in Indonesia, both before independence until post-independence Indonesia. Since the first half of the 19th century, the history of Islamic education in Indonesia has begun a new phase marked by shifts and changes in almost all aspects including institutions, methods, curriculum and Islamic education orientation. At that time Islamic education was dominated by traditional educational institutions, namely boarding schools. Islamic education is an integral part of the National Education System. As part of the national education system, Islamic education gets legitimacy for sexuality and has a place to live and develop in Indonesia to meet the educational needs of the Islamic community as a majority citizen. State accommodation for the Islamic education system makes Islamic education systems and institutions have a strong foundation to be developed by supporting funds and attention from the state. Therefore, the state is obliged to develop an Islamic education system as one of the types of religious education in the national education system.